Water vapor exposure chamber for constant humidity and hydrogen and oxygen stable isotope composition. (9th December 2018) - Oerter, Erik J.; Singleton, Michael; Thaw, Melissa; Davisson, M. Lee
Abstract : Rationale: Water vapor exposure experiments have applications for studying water physisorption and chemisorption hydration and hydroxylation reactions on a wide variety of material surfaces. The stable isotopes of hydrogen and oxygen in the water molecule are useful tracers of water exchange mechanisms and/or rates in such vapor exposure experiments. Methods: We designed and built a humidity chamber system that uses membrane‐mediated liquid–vapor exchange of water followed by mixing with dry air to control the relative humidity of air and its δ 2 H and δ 18 O isotopic composition. We tested the stability and precision of the humidity and its isotopic composition on hourly to 90‐day timescales. Results: The humidity chamber design reported here is capable of providing relative humidity control to within ±1%, and consistent δ 2 H and δ 18 O values of the water vapor that are similar to our cavity ringdown spectroscopy (CRDS) measurement precision (δ 2 Hvap  ± 0.7‰ and δ 18 Ovap  ± 0.24‰). We quantify the isotopic enrichment effects of Rayleigh distillation in the system and provide information on water reservoir sizes large enough to buffer isotopic enrichment effects to within measurement precision. Conclusions: The humidity chamber design reported here provides a means to create constant δ 2 H and δ 18 O values over the course of an exposure experiment. The design has applications to a wide range of studies of water sorption on material surfaces from foods and pharmaceuticals to geological materials.